Temporal trends in retinal detachment incidence in Scotland between 1987 and 2006. Issue 3 (7th July 2010) - Mitry, Danny; Chalmers, James; Anderson, Kirsty; Williams, Linda; Fleck, Brian W; Wright, Alan; Campbell, Harry
Abstract : Aim: Rhegmatogenous retinal detachment (RRD) is a common and sight-threatening condition. The reported incidence of RRD has varied considerably in published literature and few studies have examined the temporal trends in incidence rate over a long time period. Our aim is to examine the time trends of primary RRD in Scotland. Methods: We obtained linked hospital episode statistics data for all patients admitted with a primary diagnostic code of RRD in Scotland between 1987 and 2006. Using this database as an estimate of RRD incidence, we calculated the annual age- and sex-specific incidence rates of RRD in Scotland. Log-linear Poisson regression analysis was used to explore age, period and cohort trends. Results: The overall age-standardised incidence of RRD in Scotland has steadily increased from 9.36 per 100 000 (95% CI 8.19 to 10.53) in 1987 to 13.61 per 100 000 (95% CI 12.25 to 14.97) in 2006 with an average annual increase of 1.9% (p<0.001) during the 20-year period. Men have been affected more frequently than women in all age groups with a significant temporal trend towards earlier age of onset. The peak incidence of RRD in men and women is in the sixth decade of life. No significant period or recent birth cohort trend effects were found. Conclusions: The estimated incidence of RRD is within the range reported from previous population-based studies worldwide. The rise in RRD incidence between 1987 and 2006 is attributed in part to the changing demographic in Scotland. There is an increasing sex imbalance in incidence, with men being affected more frequently and at a younger age.